Proceso de fijación de algunas lexías complejas - Conde Salazar, Matilde (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
The aim of this article is to state that the constituents of three Latin phrasal lexems: ortis solus, mercede conductus and confirmare animum, experience a progressive integration in writers preceding Quintus Curtius Rufus, until they appear as fixed lexicalized forms in this author; and afterwards each of them have a different destiny.